2016
DOI: 10.4084/mjhid.2016.058
|View full text |Cite
|
Sign up to set email alerts
|

The Icet-a Recommendations for the Diagnosis and Management of Disturbances of Glucose Homeostasis in Thalassemia Major Patients

Abstract: Iron overload in patients with thalassemia major (TM) affects glucose regulation and is mediated by several mechanisms. The pathogenesis of glycaemic abnormalities in TM is complex and multifactorial. It has been predominantly attributed to a combination of reduced insulin secretory capacity and insulin resistance. The exact mechanisms responsible for progression from norm glycaemia to overt diabetes in these patients are still poorly understood but are attributed mainly to insulin deficiency resulting from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 68 publications
0
36
0
4
Order By: Relevance
“…Disturbances of glucose homeostasis, ranging from mild glucose intolerance to overt diabetes mellitus, and hyperinsulinism were reported in young adult patients with thalassemia and have been attributed to iron overload, HCV infection, anemia, and chronic liver disease. 66,67 An acute effect of blood transfusion on insulin sensitivity and β-cell function in patients with thalassemia has been reported by Wankanit et al 68 Alcohol and Tobacco. Alcohol and iron are known prooxidants, and oxidative stress is known to play an essential role in the development of several diseases, including cancer.…”
Section: Pathophysiology Past and Recent Issuesmentioning
confidence: 94%
“…Disturbances of glucose homeostasis, ranging from mild glucose intolerance to overt diabetes mellitus, and hyperinsulinism were reported in young adult patients with thalassemia and have been attributed to iron overload, HCV infection, anemia, and chronic liver disease. 66,67 An acute effect of blood transfusion on insulin sensitivity and β-cell function in patients with thalassemia has been reported by Wankanit et al 68 Alcohol and Tobacco. Alcohol and iron are known prooxidants, and oxidative stress is known to play an essential role in the development of several diseases, including cancer.…”
Section: Pathophysiology Past and Recent Issuesmentioning
confidence: 94%
“… 21 Because of the increased risk of glucose disturbances in β-TDT patients with iron overload, there are recommendations for annual evaluation of glycemic status in children over ten years. 22 …”
Section: Discussionmentioning
confidence: 99%
“…We included β‐TM patients with serum ferritin ≥1000 μg/L because this cutoff denotes iron‐overload and predisposes to complications. It has been linked to endocrine dysfunction and glucose abnormalities in several studies . We found that 70% of the 20 β‐TM patients with RBG ≥7.8 mmol/L had serum ferritin ≥2500 mg/dL, with a median serum ferritin of 4750 (2304.5‐6500) μg/L.…”
Section: Discussionmentioning
confidence: 99%
“…It has been linked to endocrine dysfunction and glucose abnormalities in several studies. [40][41][42] We found that 70% of the 20 β-TM patients with Abbreviations: AUC, area under the curve; β-TM, β-thalassemia major; FBG, fasting blood glucose; HOMA-IR, homeostatic model assessment insulin resistance; HBA1c, hemoglobin A1c; IQR, interquartile range; MAD, mean average deviation; PPBG: postprandial blood glucose; RBG: random blood glucose; . have abnormal glucose levels in the diabetic range and three had IGT.…”
Section: Discussionmentioning
confidence: 99%